El Niño drives timing of breeding but not population growth in the song sparrow (Melospiza melodia) - Wilson, Scott (National Academy of Sciences, 2003)
Increasing evidence suggests that climate change affects the timing of breeding in birds, but there is less evidence to show how such changes affect the population dynamics of birds overall. Over the past 43 years, song sparrows (Melospiza melodia) on Mandarte Island, British Columbia, Canada have not shown an advance in breeding date in response to global warming. However, this population did show considerable annual variation in timing of breeding correlated with the El Niño Southern Oscillation. Birds bred earlier in warmer El Niño years and later in colder La Niña years. Early breeding strongly increased reproductive output. However, annual variation in timing of breeding had little effect on population growth, perhaps because the population is strongly regulated by the rate of recruitment by juveniles. The juvenile recruitment rate declined with increasing population density but showed little response to climate. These findings suggest that populations will vary in response to climate change depending on how climate affects the demographic parameters that contribute most to population growth.